2006
DOI: 10.1189/jlb.0106048
|View full text |Cite
|
Sign up to set email alerts
|

Bovine and human cathelicidin cationic host defense peptides similarly suppress transcriptional responses to bacterial lipopolysaccharide

Abstract: Genomic approaches can be exploited to expose the complexities and conservation of biological systems such as the immune network across various mammalian species. In this study, temporal transcriptional expression profiles were analyzed in human and bovine monocytic cells in response to the TLR-4 agonist, LPS, in the presence or absence of their respective host defense peptides. The cathelicidin peptides, human LL-37 and bovine myeloid antimicrobial peptide-27 (BMAP-27), are homologs, yet they have diverged no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 48 publications
4
78
0
Order By: Relevance
“…Despite substantial overlap (Ͼ30%) in the gene responses to LL-37 and IDR-1, both in the absence and presence of the TLR-4 agonist LPS (17,19,20), there are clear differences in functions mediated by these peptides. For example, LL-37 is a modulator of apoptosis in epithelial cells (43,44) and neutrophils (32) and causes degranulation of mast cells (22), whereas IDR-1 does not (17).…”
Section: Discussionmentioning
confidence: 99%
“…Despite substantial overlap (Ͼ30%) in the gene responses to LL-37 and IDR-1, both in the absence and presence of the TLR-4 agonist LPS (17,19,20), there are clear differences in functions mediated by these peptides. For example, LL-37 is a modulator of apoptosis in epithelial cells (43,44) and neutrophils (32) and causes degranulation of mast cells (22), whereas IDR-1 does not (17).…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of gamma interferon (IFN-␥) and tumor necrosis factor alpha (TNF-␣) in culture supernatants were determined by capture enzyme-linked immunosorbent assays (ELISAs) as described previously (28,29). Net cytokine secretion was calculated by subtracting the level of spontaneous cytokine release from cells cultured in medium alone from the level of cytokine release induced by stimulation with the M. avium subsp.…”
Section: Methodsmentioning
confidence: 99%
“…Cathelicidin peptides such as LL-37, BMAP-28 and mimetics IDR-1 and IDR-1002 have been shown to suppress specific pro-inflammatory responses such as induction of tumour necrosis factor (TNF)-α, IL-1β, NF-ĸB1 (p105/p50), TNF-α-induced protein-2, MMP-3 and nitric oxide in the presence of either pathogenic or immune-mediated inflammatory stimuli, without suppressing production of certain chemokines that are required for cell recruitment and movement. In contrast, these peptides enhance or maintain crucial anti-inflammatory responses such as TNF-α-induced protein-3 (also known as A20), the NF-ĸB inhibitor NFĸBIA, expression of IL-10 and the IL-1 antagonist IL-1RA [10,11,15,20,35,36,37]. Mechanistic studies to date have demonstrated that the anti-inflammatory or immunomodulatory activity of these peptides is very complex and involves intracellular uptake, endocytic mobilization and interaction with several receptors, resulting in altered signalling pathways (such as NF-ĸB, p38 and JNK MAPK, and PI3K) and transcription factor activities with different kinetics.…”
Section: Modulation Of Inflammationmentioning
confidence: 99%